Taxonomical and functional analyses of epifaunal polychaetes associated with Mussismilia spp.: the effects of coral growth morphology - Nogueira,Marcos; Magalhães,Wagner; Mariano-Neto,Eduardo; Neves,Elizabeth; Johnsson,Rodrigo (PeerJ, 2023)
Background The increasing habitat heterogeneity and complexity shows positive effects over different communities, leading to environmental diversity, access to resources and reducing the effectiveness of predation. In the present study we evaluate the structural and functional patterns of polychaete assemblages of three Mussismilia species with different coral morphology. Mussismilia hispida has a massive growth pattern; M. braziliensis also is a massive coral but forms a crevice in the corallum base; and M. harttii has a meandroid pattern. Methods Ten individuals of the three Mussismilia species were sampled in two reefs in the Todos-os-Santos Bay, and we analyzed the differences in richness and abundance of polychaete species and the functional diversity metrics: Rao’s quadratic entropy, functional dispersion, functional evenness, number of functional groups and functional richness, among Mussismilia species. Results Two-way ANOVA with permutations showed significant differences for polychaete abundances and richness among Mussismilia species (higher values for M. harttii), but no differences were recorded when compared between the two coral reef areas studied. There was no statistical difference among coral species or between reefs in relation to the functional diversity components influenced by abundance, such as Rao quadratic entropy, functional dispersion, and functional evenness. Some individual polychaete functional traits presented differences among Mussismilia species, and that also helped us to build a picture about the effect of different growth structures over functional aspects of polychaete assemblages. Thus, the taxonomical approach, the analysis of individual functional traits and the functional diversity metrics are fundamental tools to characterize the assemblage of organisms associated with corals.
Keywords: Interaction; Association; Refuge; Habitat complexity; Habitat structure; Functional diversity